Peranan Wakaf Produktif Pemuda Muhammadiyah Untuk Kesejahteraan Warga Desa Longkeyang, Bodeh, Pemalang - Bakhri, Amirul (Kopertais Wilayah X Jawa Tengah, 2017)
AbstractOne of the forms of worship to draw closer to Allah SWT related to property is donated. waqf istismari also called productive waqf, waqf property that is used for investment purposes, whether in agriculture, industry, trade, and services. This endowment is growing problems in the village Longkeyang, where the youth of Longkeyang attempted endowment for the welfare of citizens. In 2006, approximately 10 people from the youth of the Longkeyang together activists AMM (Angkatan Muda Muhammadiyah) began a new initiative is to create a new institution that was later (in 2010) was named after the Badan Pekerja Pengembangan Ranting Muhammadiyah (BP2RM). (1) The first step movement endowment productive Muhammadiyah Youth in Longkeyang namely (a) the anxiety of citizens and youth of the organization is stagnant and also go hand in hand some scholars who died, so no worries